Assessing Student Engagement in Qurdis Subject Using Wordwall: Menilai Keterlibatan Siswa dalam Mata Pelajaran Qurdis Menggunakan Wordwall - Alfi, Badrina; Lismawati, Lismawati (Halaqa: Islamic Education Journal, 2024)
This research aims to measure the impact of using Wordwall-assisted learning media on improving student learning outcomes in class This research uses a quantitative type of experimental method with a One Group Pretest and Posttest design, which was conducted at MAN 19 Jakarta in December with 68 class X students as the target subjects. Data collection used Pre-test (question and answer) and Post-test (books and wordwall) to the experimental group and control group. Data analysis techniques were carried out using SPSS parametric tests, namely descriptive analysis, normality test, homogeneity test, paired simple t test, independent t test. The results of the parametric test showed that the average value of the experimental group was 87.68 with a standard deviation of 5,079 and the control group was 76.18 with a standard deviation of 7,453. So the wordwall learning media has a big influence on student learning outcomes in measuring involvement in the teaching and learning process. And these findings show that the use of Wordwall as a learning medium can make a positive contribution to student achievement, providing a basis for teachers to integrate technology in their teaching. Keywords: Learning Media, Wordwall, Learning Results